AHP-Based Analysis Factors Influencing the Construction of a Smart City with Three-Dimensional Regional Color. (27th November 2021) - Yang, Xiaofei; Ma, Lini
Abstract : Urban color is becoming more and more important in the construction of smart cities. This research mainly discusses the influencing factors of AHP-based 3D regional color smart city construction. From the perspective of city managers, the factors selected in the article that affect the choice of urban color planning are economic development, urban culture, designer's ideas, customs, and natural environment. We use GIS to comprehensively collect basic geographic information data of the city. We use CityEngine and GIS data to quickly create virtual cities. When constructing the AHP model, once the weight value of each factor in the color-influencing factors of the entire smart city is obtained, the total ranking of the levels needs to be checked once. After that, the study uses the MATLAB program platform to realize the parametric design of the main color of the city, including the control of the changes in the spatial structure of the main color of the city, followed by the control of the transition and coordination mode between the key elements of the city color. Explorer provides comprehensive and rich 3D digital city roaming browsing, query positioning, analysis, and other functions; supports the loading of multiple data sets from the Internet and local; and can dynamically load massive 3D city simulation models above and below ground. Finally, the design of the urban architectural color or improvement plan is further carried out, and the urban color main color design plan is finally implemented in the implementation of the urban architectural color, which effectively realizes the quantitative control of the urban color. When evaluating smart city color resources, the color weight value of public facilities is 0.147, which accounts for 14.7% of the total weight value. This research helps to enhance the regional and local cultural characteristics.